2020
DOI: 10.1093/conphys/coaa049
|View full text |Cite
|
Sign up to set email alerts
|

Basal tolerance but not plasticity gives invasive springtails the advantage in an assemblage setting

Abstract: As global climates change, alien species are anticipated to have a growing advantage relative to their indigenous counterparts, mediated through consistent trait differences between the groups. These insights have largely been developed based on interspecific comparisons using multiple species examined from different locations. Whether such consistent physiological trait differences are present within assemblages is not well understood, especially for animals. Yet, it is at the assemblage level that interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 82 publications
2
30
2
Order By: Relevance
“…In our review, only ∼23 % of publications provide information about the generation used in the experiments (Table A1), thus we can only assume that for the rest they are the original, field-collected specimens. Recent studies have observed no significant differences in thermal tolerance or another type of stress-tolerance metric between field-collected and second-generation individuals ( Phillips et al., 2020 ; Maclean et al., 2018 ), but this is not always the case as investigations of laboratory adaptation and intergenerational effects have demonstrated ( Sgrò and Partridge, 2000 ; Hoffmann et al., 2017 ). First, the rearing of animals in the laboratory enables control of certain factors than can affect thermal tolerance, such as the age of individuals ( Alemu et al., 2017 ) or their feeding status ( Nyamukondiwa and Terblanche, 2009 ).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In our review, only ∼23 % of publications provide information about the generation used in the experiments (Table A1), thus we can only assume that for the rest they are the original, field-collected specimens. Recent studies have observed no significant differences in thermal tolerance or another type of stress-tolerance metric between field-collected and second-generation individuals ( Phillips et al., 2020 ; Maclean et al., 2018 ), but this is not always the case as investigations of laboratory adaptation and intergenerational effects have demonstrated ( Sgrò and Partridge, 2000 ; Hoffmann et al., 2017 ). First, the rearing of animals in the laboratory enables control of certain factors than can affect thermal tolerance, such as the age of individuals ( Alemu et al., 2017 ) or their feeding status ( Nyamukondiwa and Terblanche, 2009 ).…”
Section: Resultsmentioning
confidence: 94%
“…The aim of this work is to review the current state of scientific knowledge on thermal tolerance limits in Collembola, given their significance in the soil fauna, their global distribution, and the apparent differences in thermal tolerance traits between indigenous and introduced species in local assemblages and at broader spatial scales ( Janion-Scheepers et al., 2018 ; Phillips et al., 2020 ). Thermal tolerance data become of great help to manage those areas that species may or may not occupy under changing climates ( Evans et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, P. pratensis , while managed to acclimatize to the harsh conditions of Cierva Point, was not able to adapt towards reproducing effectively in such conditions. Most of the non-native invertebrates (Diptera and Collembola) introduced to the continent also possess good cold-tolerance capabilities (Bahrndorff et al 2009, Bartlett et al 2019a, Liu et al 2020, Phillips et al 2020) that make them readily adaptable to their Antarctic environments (Worland 2010). In the case of the dipteran T. maculipennis , representing the latest threat, recent studies have confirmed the capacity of its larvae to withstand temperatures down to -5°C for short periods (Pertierra et al 2021), while the northern boreal parts of its native distribution expose it to similar or more severe thermal stresses than characterize its establishment locations on King George Island (Remedios-de León et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In the sub-Antarctic, arthropods have evolved under chronically low but relatively stable environmental conditions (in terms of limited annual thermal variation and high relative humidity; Convey, 1996aConvey, , 1996b. They are thus expected to exhibit stenotypic characteristics, and a level of thermal adaptation to their native ecoregion, whereas non-native incoming species, typically originating from temperate (often boreal) regions are likely to exhibit more generalist eurythermal characteristics (Barendse & Chown, 2000;Chown & Convey, 2016;Phillips et al, 2020;Slabber et al, 2007).…”
Section: Introductionmentioning
confidence: 99%